ASSET TURNOVER, LEVERAGE, AND ROA: THE MODERATING ROLE OF FIRM SIZE IN ASEAN TECHNOLOGY FIRMS - Vanda Sherlita Ardelia; Loggar Bhilawa (Majapahit Journal of Islamic Finance and Management, 2026)
This study examines the effect of Asset Turnover (ATO) and Debt to Equity Ratio (DER) on firm performance, proxied by Return on Assets (ROA), with firm size as a moderating variable in technology companies. The background of this research is the burn money phenomenon commonly observed in technology firms, where companies prioritize aggressive growth over short-term profitability, potentially affecting financial performance. The purpose of this study is to analyze the direct influence of ATO and DER on ROA and to determine whether firm size moderates these relationships. This research employs a quantitative approach using secondary data from financial statements, analyzed through multiple regression and moderated regression analysis (MRA). The results show that ATO has a positive effect on ROA, while DER has a negative effect. However, firm size is not proven to significantly moderate these relationships. Additionally, the relatively low coefficient of determination (R²) indicates that other factors beyond the model may have a greater influence on firm performance. In conclusion, although ATO and DER affect ROA, their explanatory power is limited, and firm size does not play a strong moderating role.